Aberrant topologies and reconfiguration pattern of functional brain network in children with second language reading impairment. Issue 4 (19th June 2016) - Liu, Lanfang; Li, Hehui; Zhang, Manli; Wang, Zhengke; Wei, Na; Liu, Li; Meng, Xiangzhi; Ding, Guosheng
Abstract: Prior work has extensively studied neural deficits in children with reading impairment (RI) in their native language but has rarely examined those of RI children in their second language (L2). A recent study revealed that the function of the local brain regions was disrupted in children with RI in L2, but it is not clear whether the disruption also occurs at a large‐scale brain network level. Using fMRI and graph theoretical analysis, we explored the topology of the whole‐brain functional network during a phonological rhyming task and network reconfigurations across task and short resting phases in Chinese children with English reading impairment versus age‐matched typically developing (TD) children. We found that, when completing the phonological task, the RI group exhibited higher local network efficiency and network modularity compared with the TD group. When switching between the phonological task and the short resting phase, the RI group showed difficulty with network reconfiguration, as reflected in fewer changes in the local efficiency and modularity properties and less rearrangement of the modular communities. These findings were reproducible after controlling for the effects of in‐scanner accuracy, participant gender, and L1 reading performance. The results from the whole‐brain network analyses were largely replicated in the task‐activated network. These findings provide preliminary evidence supporting that RI in L2 is associated with not only abnormal functional network organization but also poor flexibility of the neural system in responding to changing cognitive demands. Abstract : We explored the large‐scale functional brain network in children with L2 reading impairment (RI) versus typically developing (TD) children. We found RI children exhibited abnormally over‐clustered topology in their whole‐brain network in a phonological task, and showed difficulty with network reconfiguration when switching between the phonological task and short resting phases. These results indicate L2 reading impairment may be associated with a developmental lag and lack of flexibility in brain system.